The Internal Control System Analysis on the Effectiveness of Cash Receipts at Pt Pln (Persero) Kendari Branch - Resky, Kartika; Lisaply, David; Hamid, Hamzah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to evaluate the effectiveness and efficiency of internal control over cash flow within PT PLN (Persero) Kendari Branch, a State-Owned Enterprise (BUMN) in Indonesia. Effective internal control is essential to monitor both cash inflows and outflows and to support the implementation of financial policies that align with organizational objectives. The core issue addressed in this study is the adequacy of the internal control system for cash receipts and the overall effectiveness of cash receipt processes. A descriptive analysis method was employed to assess current practices. The findings reveal that the internal control system related to cash receipts is generally adequate, as evidenced by the clear separation of duties and responsibilities between the account recording function and the cash receipt function. However, regarding the effectiveness of cash collection, the use of the Payment Point Online Bank (PPOB) system has paradoxically led to an increase in the number of customers delaying payments. This suggests that while internal control mechanisms are in place, further improvements are needed in ensuring timely cash collection.